Employee Performance Improvement Strategy at Arung Palakka Bone Airport - M. Awaluddin A (Jurnal Office, 2021)
This research was conducted to find out the strategies implemented in improving employee performance at Arung Palakka Bone Airport. And to find out the effectiveness of implementing employee performance improvement strategies at Arung Palakka Bone Airport.  the type of research used is qualitative research with a case study approach. because the author wants to describe and analyze employee performance improvement strategies at Arung Palakka Bone Airport. This research was conducted at the Arung Palakka Airport Office, Bone District, Awangpone District, Bone District, Airport Road, Mappalo Ulaweng Village. Employee performance improvement strategies are important actions for companies or organizations in an effort to increase productivity, efficiency and quality of work. However, the effectiveness of implementing this strategy depends on various factors, such as the availability of resources, employee involvement, effective leadership, organizational culture , and employee competence. Therefore, Arung Palakka Bone Airport must ensure that employee performance improvement strategies are implemented consistently and evenly for all employees, and ensure that any obstacles that may arise can be properly addressed. Thus, the effectiveness of implementing employee performance improvement strategies is a very important factor for the success of a company or organization, and must be considered carefully so that the goals set can be achieved effectively and efficiently. Research can be used as a reference in determining employee performance improvement strategies in government agencies in general.